(untitled) (Journal of Nonlinear Modeling and Analysis, 2024)
This paper introduces an equality that is valid for tempered fractional integrals. By using this equality, we establish some Euler-Maclaurin-type inequalities for the case of differentiable convex functions involving tempered fractional integrals. Furthermore, our results are provided by using special cases of obtained theorems.